LEAK CURRENT DETECTOR IN LOW VOLTAGE NETWORK (JTR) SYSTEM USING ZMPT101B SENSOR BASED ON THE INTERNET OF THINGS (IoT) - Laisina, Luwis H. (Information Technology and Science (ITScience), 2023)
Phase-to-ground leakage in low-voltage network systems can cause transformer damage due to overload. Overloading on transformers is not caused by customer usage but rather by wasted electrical energy to the ground which causes losses. If there is a current leakage, the potential difference between neutral and ground is measured to produce a voltage value. Considering that there is little written about transformer damage caused by current leakage to ground in low voltage network systems, in this research a tool is made that can detect current leakage to ground in low voltage network systems using the ZMPT101B voltage sensor based on IoT. This research is in the form of design and manufacture of a leakage current detector to ground. The method used is the Research and Development method (research and development), namely in the form of observation, literature study. The research stage starts from a literature study in the form of finding references related to research, designing tools, making tools and programs, and testing the tools that are made. Based on the results of Based on the results of the research, this tool can detect leakage current to the ground from the lowest voltage of 24.3 Volts to the highest voltage of 184 Volts so that it can be displayed on the LCD and the blynk application and the system automatically sounds a buzzer as a warning of current leakage to ground. .